Aphasia Park: A pilot study using the co-active therapeutic theater model with clients in aphasia recovery. (February 2020) - Wood, Laura L.; Bryant, Dani; Scirocco, Kerryann; Datta, Hia; Alimonti, Susan; Mowers, Dave
Highlights: Applied Thematic Analysis was used to analyze the perceived benefits of creating therapeutic theater opportunities with clients with aphasia. Using co-active therapeutic theater with persons with Aphasia resulted in social-emotional and speech benefits. There is valuable collaboration to be had between drama therapy and speech language pathology. Abstract: Aphasia, most often caused by brain damage due to stroke, is a language disorder hindering one's ability to verbally express and/or comprehend language, ranging in severity from mild to severe. An Applied Thematic Analysis (ATA) was undertaken of a post-production focus group to evaluate a 12-week pilot program that used the CoActive Therapeutic Theater (CoATT) Model for persons in Aphasia recovery. Results of a focus group interview found five themes that participants noted as unique outcomes following participation in the pilot program: 1) Meaningful relationships; 2) Increased belief in self; 3) Invigorating experience; 4) Unique healing opportunity; 5) Perceived speech and language improvement.